DATA-DRIVEN STRATEGY: HOW BIG DATA SAVES TOURIST DESTINATIONS FROM ENVIRONMENTAL DEGRADATION - Sugih Prakoso; Sandi Setiadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to optimize digital tourism strategies in the Puncak region, West Java, in support of achieving the Sustainable Development Goals (SDGs), particularly inclusive economic growth and environmental preservation. The study uses a quantitative approach with an explanatory research design and involves 225 digital tourists as respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that both User-Generated Content and Digital Sentiment Analysis positively and significantly influence Tourism Sustainability, not only directly but also through the mediation of a Digital Tourism Strategy. Digital Sentiment Analysis has the most dominant influence on the formation of digital strategies, as indicated by a t-statistics value of 13.903. In addition, the model has a very strong predictive power, where Digital Tourism Strategy is able to explain 92.2% of the variance in Tourism Sustainability. Overall, these findings emphasize the importance of integrating tourist digital data and sentiment analytics as the basis for formulating adaptive, evidence-based tourism policies that are oriented towards destination sustainability and the balance of the national tourism ecosystem.